2007
DOI: 10.1007/s00125-007-0841-7
|View full text |Cite
|
Sign up to set email alerts
|

Fat depot-related differences in gene expression, adiponectin secretion, and insulin action and signalling in human adipocytes differentiated in vitro from precursor stromal cells

Abstract: Aim/hypothesis The distinct metabolic properties of visceral and subcutaneous adipocytes may be due to inherent characteristics of the cells that are resident in each fat depot. To test this hypothesis, human adipocytes were differentiated in vitro from precursor stromal cells obtained from visceral and subcutaneous fat depots and analysed for genetic, biochemical and metabolic endpoints. Methods Stromal cells were isolated from adipose tissue depots of nondiabetic individuals. mRNA levels of adipocytespecific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
104
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(122 citation statements)
references
References 37 publications
9
104
0
6
Order By: Relevance
“…Consistent with our data, the study by Drolet et al 12 showed no difference in total adiponectin secretion between subcutaneous and omental adipocytes in subjects with a wide range of BMI, with an exception of a subgroup of visceral obese who presented lower omental cell adiponectin release when compared with subcutaneous cells. Motoshima et al 11 and Perrini et al 3 reported that the cultured human omental adipocytes secrete more adiponectin than subcutaneous adipocytes and that its secretion is inversely correlated to BMI, whereas the secretion from the subcutaneous cells was unrelated to BMI. Contrary to this, Phillips et al 29 showed lower adiponectin levels secreted by VAT than SAT explants of obese as well as type 2 diabetic people.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our data, the study by Drolet et al 12 showed no difference in total adiponectin secretion between subcutaneous and omental adipocytes in subjects with a wide range of BMI, with an exception of a subgroup of visceral obese who presented lower omental cell adiponectin release when compared with subcutaneous cells. Motoshima et al 11 and Perrini et al 3 reported that the cultured human omental adipocytes secrete more adiponectin than subcutaneous adipocytes and that its secretion is inversely correlated to BMI, whereas the secretion from the subcutaneous cells was unrelated to BMI. Contrary to this, Phillips et al 29 showed lower adiponectin levels secreted by VAT than SAT explants of obese as well as type 2 diabetic people.…”
Section: Discussionmentioning
confidence: 99%
“…Even in adipocytes differentiated in vitro from precursor mesenchymal cells, adiponectin expression is lower in visceral adipocytes than subcutaneous adipocytes [56].…”
Section: Adiponectinmentioning
confidence: 92%
“…[6][7][8] The particular importance of visceral fat accumulation versus subcutaneous fat depot dysfunction has recently been challenged 9,10 as there is mounting evidence to support that visceral adipocytes are phenotypically different from subcutaneous adipocytes. 11 Nevertheless, it is the protective role of lower body, that is, gluteofemoral fat that is striking. The protective properties of the lower-body fat depot have been confirmed in many studies conducted in subjects with a wide range of age, BMI and co-morbidities (Table 1).…”
Section: Body Fat Distribution and Riskmentioning
confidence: 99%
“…Differences in expression of adipokine genes and in secretion in vitro are well established when comparing subcutaneous and visceral fat. 11,58 However, little is known regarding differences between upper-and lower-body fat.…”
Section: Adipokine Formation In Regional Adipose Tissuementioning
confidence: 99%